2020
DOI: 10.3390/app10020649
|View full text |Cite
|
Sign up to set email alerts
|

A Novel GPU-Based Acceleration Algorithm for a Longwave Radiative Transfer Model

Abstract: Graphics processing unit (GPU)-based computing for climate system models is a longstanding research area of interest. The rapid radiative transfer model for general circulation models (RRTMG), a popular atmospheric radiative transfer model, can calculate atmospheric radiative fluxes and heating rates. However, the RRTMG has a high calculation time, so it is urgent to study its GPU-based efficient acceleration algorithm to enable large-scale and long-term climatic simulations. To improve the calculative efficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…These architectures include the residual blocks proposed in ResNet (He et al, 2015b) and the depth-wise separable convolution used in MobileNets (Howard et al, 2017) and Xception (Chollet, 2016), among others. Furthermore, EfficientNet (Tan and Le, 2019) has shown that an efficient balancing of network depth, width, and resolution can lead to better performance in terms of prediction accuracy and speed. However, any such reduction of model parameters in CNNs or exploring newer architectures must be accompanied with a rigorous validation procedure, which could be similar to the workflow proposed above.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These architectures include the residual blocks proposed in ResNet (He et al, 2015b) and the depth-wise separable convolution used in MobileNets (Howard et al, 2017) and Xception (Chollet, 2016), among others. Furthermore, EfficientNet (Tan and Le, 2019) has shown that an efficient balancing of network depth, width, and resolution can lead to better performance in terms of prediction accuracy and speed. However, any such reduction of model parameters in CNNs or exploring newer architectures must be accompanied with a rigorous validation procedure, which could be similar to the workflow proposed above.…”
Section: Discussionmentioning
confidence: 99%
“…Recent advances in NNs have led to rapid progress in the accuracy of pattern and image recognition tasks. In particular, convolutional neural networks (CNNs) (Krizhevsky et al, 2012a) have achieved impressive results for image classification (Krizhevsky et al, 2012b), while recurrent neural networks (RNNs) have made breakthroughs in sequenceto-sequence learning tasks such as machine translation (Wu et al, 2016). Efforts to use machine learning techniques to model actual physical processes in a climate model have increased recently (Schneider et al, 2017;Gentine et al, 2018;Rasp et al, 2018;O'Gorman and Dwyer, 2018;Scher, 2018;Bretherton, 2018, 2019;San and Maulik, 2018;Yuval and O'Gorman, 2020).…”
Section: Introductionmentioning
confidence: 99%